Membangun Daya Saing Industri Kecil dengan Kompetensi dan Faktor Eksternal Melalui Strategi dan Kinerja Bisnis - Saputra, Jeffriansyah; Suryati, Tri Frida (LPPM Universitas Muhammadiyah Mamuju, 2022)
This study aims to determine the dimensions of competence and external factors affect the competitiveness of small industries both directly and indirectly through business strategy and performance. This type of research is explanatory, this study uses 11 variables and 30 indicators so that the number of latent variables is 41 pieces. The study sampling used a minimum sample count of 205 small industries in South Sulawesi from structural equation modelling analysis for maximum likehood estimation. The results of this study state that competence and external factors have a significant and positive influence on competitiveness both directly and indirectly through business strategies and performance in building the competitiveness of small industries in South Sulawesi.